1982
DOI: 10.1083/jcb.92.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Action of cytochalasin D on cytoskeletal networks.

Abstract: Extraction of BSC-1 cells (African green monkey kidney) with the detergent Triton X-100 in combination with stereo high-voltage electron microscopy of whole mount preparations has been used as an approach to determine the mode of action of cytochalasin D on cells. The cytoskeleton of extracted BSC-1 cells consists of substrate-associated filament bundles (stress fibers) and a highly cross-linked network of four major filament types extending throughout the cell body : 10-nm filaments, actin microfilaments, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
359
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(395 citation statements)
references
References 32 publications
30
359
2
3
Order By: Relevance
“…While this interaction may serve as a means to control the spatial distribution of ion channels in the apical membrane of epithelial cells, a requirement in polarized epithelia, the possibility also existed that the colocalization of actin filaments with the apical Na ϩ channels would serve a functional role. Modification of actin filament organization with cytochalasin D, an actin filament disrupter (41)(42)(43), induced apical Na ϩ channel activity in the A6 cell (15). Because DNase I, which inhibits actin polymerization, inhibited the cytochalasin D-induced Na ϩ channel activity, the data suggested that "short" actin filaments might be involved in effect- ing ion channel activation.…”
Section: Discussionmentioning
confidence: 97%
“…While this interaction may serve as a means to control the spatial distribution of ion channels in the apical membrane of epithelial cells, a requirement in polarized epithelia, the possibility also existed that the colocalization of actin filaments with the apical Na ϩ channels would serve a functional role. Modification of actin filament organization with cytochalasin D, an actin filament disrupter (41)(42)(43), induced apical Na ϩ channel activity in the A6 cell (15). Because DNase I, which inhibits actin polymerization, inhibited the cytochalasin D-induced Na ϩ channel activity, the data suggested that "short" actin filaments might be involved in effect- ing ion channel activation.…”
Section: Discussionmentioning
confidence: 97%
“…Prior to testing the chondrocytes, alginate beads were incubated for 3 h in control, low, medium and high concentrations of chemical agents that disrupt the three principal cytoskeletal elements (cytochalasin D for microfilaments [44] Micropipette aspiration was used to determine the viscoelastic properties of the chondrocytes, as described previously [48]. Briefly, the solution and cells were placed in a chamber that allows for the entry of a micropipette from the side [20].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that actin remodeling requires polymerization of G-actin to form F-actin. Therefore, we hypothesized that, if we inhibited the process by a pharmacological inhibitor, cytochalasin D (Cyto D), 59 we could reduce the pDNA uptake through macropinocytosis. Indeed, our experimental data revealed that pretreatment of cells with Cyto D decreased eTE in B16.F10 and HEK293 cells by 60% and 50%, respectively ( Figure 4B).…”
Section: Inhibition Of Macropinocytosis Decreased the Efficiency Of Ementioning
confidence: 99%